Unveiling the complex network of interactions in Ionic Liquids: a combined EXAFS and Molecular Dynamics approach. (May 2016) - Serva, A; Migliorati, V; Lapi, A; D'Angelo, P
Abstract: The structural properties of geminal dicationic ionic liquids ([Cn (mim)2 ]Br2 )/water mixtures have been investigated by means of extended X-ray absorption fine structure (EXAFS) spectroscopy and Molecular Dynamics (MD) simulations. This synergic approach allowed us to assess the reliability of the MD results and to provide accurate structural information about the first coordination shell of the Br - ion. We found that the local environment around the anion changes as a function of the water concentration, while it is the same independently from the length of the bridge-alkyl chain. Moreover, as regards the long-range structural organization, no tail-tail aggregation occurs with increasing alkyl chain length.